Comparing the Effectiveness of Individual Coaching, Self-Coaching, and Group Training: How Leadership Makes the Difference - Losch, Sabine; Traut-Mattausch, Eva; Mühlberger, Maximilian D.; Jonas, Eva (Frontiers in Psychology, 2016)
Few empirical studies have used a randomized controlled design to evaluate the impact of coaching, and there are even fewer that have compared coaching with other interventions. In the current field study, we investigated the relative effectiveness of coaching as an intervention to reduce procrastination. In a randomized controlled study, participants (N = 84) were assigned to an individual coaching, a self-coaching, a group training, or a control group condition. Results indicate that individual coaching and group training were effective in reducing procrastination and facilitating goal attainment. Individual coaching created a high degree of satisfaction and was superior in helping participants attaining their goals, whereas group training successfully promoted the acquisition of relevant knowledge. The results for the self-coaching condition show that independently performing exercises without being supported by a coach is not sufficient for high goal attainment. Moreover, mediation analysis showed that a coach’s transformational and transactional leadership behavior influenced participants’ perceived autonomy support and intrinsic motivation, resulting in beneficial coaching outcomes. The results may guide the selection of appropriate human resource development methods: If there is a general need to systematically prepare employees to perform on specific tasks, group training seems appropriate due to lower costs. However, when certain aspects of working conditions or individual development goals are paramount, coaching might be indicated. However, further research is needed to compare the relative effectiveness of coaching with other interventions in different contexts.